ANALISIS KESALAHAN PENGGUNAAN ANGGAH UNGGUHING BASA BALI DALAM TEKS LOMBA PIDARTA BALI SISWA SMA/SMK SE-BALI DI UNIVERSITAS PGRI MAHADEWA INDONESIA - I Nyoman Astawan; I Nyoman Sadwika; I Dewa Putu Juwana (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The ability to communicate using good and correct Balinese orally and in writing is the main goal of teaching Balinese. In written language and formal situations, such as the language used in the Balinese pidarta text, the standard Balinese language should be used, namely good and correct language. Based on the title, the discussion in this study is about the use of Balinese language in the Balinese pidarta text which is assessed from the level of phonology and morphology. The purpose of this study was to obtain a clear understanding of the errors in the use of Balinese language in the Balinese pidarta text. From the results of the analysis, it was concluded that the errors made by students were in the use of Balinese language from the phonological level as many as 19 or 39.58% and morphology as much as 29 or 60.42%. Based on the results of the study, (1) students should learn and practice more in applying the use of Balinese language which includes phonological and morphological levels. (2) teachers are advised to provide more and more frequent exercises in applying the use of Balinese language. (3) the school is advised to further improve the facilities and infrastructure by providing a guidebook for the use of the Balinese language.